Further new complex daphniphyllum alkaloids from the stems and leaves of Daphniphyllum calycinum: Structure and stereochemistry. Issue 49 (4th December 2020) - Shen, Shou-Mao; Li, Heng; Wang, Jian-Rong; Zeng, Yan-Bo; Guo, Yue-Wei
Abstract: Four new daphniphyllum alkaloids, namely daphnicalycines A–D (1 –4 ), together with nineteen known related ones (5 –7 and 11 –26 ), were isolated from the stems and leaves of Daphniphyllum calycinum . Their structures including the absolute configurations were unambiguously elucidated by extensive spectroscopic analysis, X-ray diffraction analysis and comparison with the reported data. In particular, with the assistance of X-ray diffraction analysis, we were able not only, for the first time, to give full 1 H and 13 C NMR assignment of daphniteijsmanine (7 ) and to elucidate its absolute stereochemistry, but also lead to correct the structure of caldaphnidine E (9 ). The confusions reported for 1 and daphnimacropine (8 ) in the literature were also clarified. Graphical abstract: Image 1 Highlights: Twenty-three daphniphyllum alkaloids, of which four are new (1 –4 ), were isolated from the plant Daphniphyllum calycinum. The absolute configurations of 1, 2 and 5 –7 were unambiguously determined by X-ray diffraction analysis. The structure of caldaphnidine E (9 ) was corrected as that of daphniteijsmanine (7 ). The confused information regarding the structures of 1 and daphnimacropine (8 ) in the literature was also clarified.